A systematic review of physical illness, functional disability, and suicidal behaviour among older adults. (1st February 2016) - Fässberg, Madeleine Mellqvist; Cheung, Gary; Canetto, Silvia Sara; Erlangsen, Annette; Lapierre, Sylvie; Lindner, Reinhard; Draper, Brian; Gallo, Joseph J.; Wong, Christine; Wu, Jing; Duberstein, Paul; Wærn, Margda
Abstract : Objectives: To conduct a systematic review of studies that examined associations between physical illness/functional disability and suicidal behaviour (including ideation, nonfatal and fatal suicidal behaviour) among individuals aged 65 and older. Method: Articles published through November 2014 were identified through electronic searches using the ERIC, Google Scholar, PsycINFO, PubMed, and Scopus databases. Search terms used were suicid* or death wishes or deliberate self-harm. Studies about suicidal behaviour in individuals aged 65 and older with physical illness/functional disabilities were included in the review. Results: Sixty-five articles (across 61 independent samples) met inclusion criteria. Results from 59 quantitative studies conducted in four continents suggest that suicidal behaviour is associated with functional disability and numerous specific conditions including malignant diseases, neurological disorders, pain, COPD, liver disease, male genital disorders, and arthritis/arthrosis. Six qualitative studies from three continents contextualized these findings, providing insights into the subjective experiences of suicidal individuals. Implications for interventions and future research are discussed. Conclusion: Functional disability, as well as a number of specific physical illnesses, was shown to be associated with suicidal behaviour in older adults. We need to learn more about what at-risk, physically ill patients want, and need, to inform prevention efforts for older adults.